Physical activity and bone mineral acquisition in peripubertal girls - Lehtonen-Veromaa, M.; Mottonen, T.; Svedstrom, E.; Hakola, P.; Heinonen, O. J.; Viikari, J. (Scandinavian Journal of Medicine & Science in Sports, 2000)
The association of the amount and type of physical activity with bone mineral acquisition was studied in 191 peripubertal Caucasian girls aged 9-16 years (66 gymnasts, 65 runners, and 60 nonathletic controls). Weight, height, stage of puberty, the amount of leisure-time physical activity, and years of training were recorded, and dietary calcium and vitamin D were assessed by a semi-quantitative questionnaire. The bone area, the bone mineral density (BMD), and the bone mineral content (BMC) of the femoral neck, lumbar spine and antebrachium were measured by dual-energy x-ray absorptiometry. The unadjusted mean values of BMD at the femoral neck were 15.2% higher in the pubertal gymnasts than in the controls (P<0.001). Compared with the controls, the mean BMC adjusted for bone area of the pubertal gymnasts at the femoral neck and lumbar spine was 16.4% and 10.8% higher, respectively. When comparing the association of the type of physical activity among the pubertal athletics by multiple regression analysis, height, physical activity, gymnastics, and Tanner stage emerged as significant variables and accounted for 54.7% and 63.4% of the total variation in BMD of the femoral neck and lumbar spine, respectively. These results indicate that physical activity is associated with bone mineral acquisition in peripubertal girls and that high-impact weight-bearing exercise seems to be particularly associated with the increase of the BMD at the femoral neck.